Multiomics Study Reveals Enterococcus and Subdoligranulum Are Beneficial to Necrotizing Enterocolitis - Lin, Hao; Guo, Qingqing; Ran, Yun; Lin, Lijian; Chen, Pengcheng; He, Jianquan; Chen, Ye; Wen, Jianbo (Frontiers in Microbiology, 2021)
Necrotizing enterocolitis (NEC) is a life-threatening disease for premature infants with low body weight. Due to its fragile gut microbiome and successful treatment of fecal microbiota transplantation (FMT) for intestinal disease, we aimed to reveal the multiple-omics changes after FMT and/or sulperazone treatment. In this study, 2-week-old newborn rabbits were used to simulate the NEC model and grouped into healthy control, NEC, sulperazone treatment, FTM treatment, and FMT and sulperazone combination treatment. We evaluated the intestinal pathology and survival to define the benefit from each treatment and performed microbiome and transcriptome analysis to reveal the changes in microcosmic level, which could be helpful to understand the pathogenesis of NEC and develop new strategy. We found NEC rabbits benefit more from the combination of FMT and sulperazone treatment. Combination treatment reverses a lot of microorganisms dysregulated by NEC and showed the most similar transcript profiler with healthy control. Moreover, a combination of FMT and sulperazone significantly prolonged the survival of NEC rabbits. Function enrichment showed that metabolism and viral life cycle are the most significant changes in NEC. FMT is a common therapy method for NEC. Meanwhile, in the severe situation of NEC with intestinal infection, the first therapy strategy is preferred the third-generation cephalosporin, among which sulperazone is used widely and the effect is remarkable. So, we used sulperazone to treat the rabbits with the NEC. In this research, we aim to explore the different effects on NEC between FMT and sulperazone as well as the combination. Considering the microbiome and transcriptome result, we make a conclusion that the Enterococcus and Subdoligranulum benefits NEC by influencing the bacterial phages and butyrate production, respectively.